2019
DOI: 10.3390/vision3020029
|View full text |Cite
|
Sign up to set email alerts
|

Contextually-Based Social Attention Diverges across Covert and Overt Measures

Abstract: Humans spontaneously attend to social cues like faces and eyes. However, recent data show that this behavior is significantly weakened when visual content, such as luminance and configuration of internal features, as well as visual context, such as background and facial expression, are controlled. Here, we investigated attentional biasing elicited in response to information presented within appropriate background contexts. Using a dot-probe task, participants were presented with a face–house cue pair, with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 98 publications
(134 reference statements)
5
10
0
Order By: Relevance
“…In sum, our findings and that of others [29,30] suggest that factors such as stimulus, task parameters, and valence might play a stronger role in biasing attention to social stimuli than previously thought, particularly in children. Controversially, our findings suggest that it is not accurate to say that faces generally/automatically capture the attentional system of humans disproportionately more so than other nonsocial stimuli.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In sum, our findings and that of others [29,30] suggest that factors such as stimulus, task parameters, and valence might play a stronger role in biasing attention to social stimuli than previously thought, particularly in children. Controversially, our findings suggest that it is not accurate to say that faces generally/automatically capture the attentional system of humans disproportionately more so than other nonsocial stimuli.…”
Section: Discussionsupporting
confidence: 65%
“…Face stimuli guide eye-movements away from targets [5] and they slow search performance when task-irrelevant [7]. Furthermore, the manual detection of a target is faster when it appears at the location of a face relative to a non-face object location [28, although, see 29,30], suggesting that participants' attention was spontaneously biased to the face region, thereby facilitating detection of targets subsequently appearing there. Similar results were found in non-autistic children, who demonstrate slower search performance in the presence of task-irrelevant upright [8] and inverted [31] faces.…”
Section: Introductionmentioning
confidence: 99%
“…Pereira and colleagues found across multiple experiments that faces did not reliably draw attention to their cued location, as indexed by participants' reaction time. In a follow-up Bayesian analysis on one of their experiments, the authors found evidence for the null hypothesis of no reaction time differences emerging for targets appearing at locations that were cued by faces or houses (Pereira et al, 2019). While a different task was used in these studies, the authors' findings closely align with ours: faces are not reliably capturing attention and impairing the performance on an unrelated cognitive task.…”
Section: General Discussion General Discussionsupporting
confidence: 62%
“…Bayesian analysis on one of their experiments, the authors found evidence for the null hypothesis of no reaction time differences emerging for targets appearing at locations that were cued by faces or houses (Pereira et al, 2019). While a different task was used in these studies, the authors' findings closely align with ours: faces are not reliably capturing attention and impairing the performance on an unrelated cognitive task.…”
Section: Discussionsupporting
confidence: 59%